(untitled) (Al-Academy, 2025)
The current research dealt with the study of the philosophy of extremism and terrorism in contemporary graphic discourse, which allows understanding how to employ graphic discourse in influencing societies, whether through the dissemination of extremist thought or confronting it with design methods, which requires the development of design treatments capable of confronting extremist discourses and enhancing societal awareness of the seriousness of the philosophy of extremism and terrorism, and thus graphic discourse has become an effective tool in shaping public opinion and influencing perception, whether in contexts and describing positive or negative phenomena. With the increasing challenges resulting from terrorism and violence, the graphic discourse was relied on as a means and tool to combat violent speech and promote the values of tolerance, moderation and rejection of violence, and according to the above, the researcher has deliberately addressed the subject withresearch and study by asking the following question: What is the philosophy of extremism and terrorism in contemporary graphic discourse? The researcher adopted the descriptive approach in the analysis of the research sample to reach the goal of the research represented in (identifying the philosophy of extremism and terrorism and its representations in the contemporary graphic discourse), and in accordance with the subject of the research because it allows the possibility of conducting analysis and inference and to serve the course of research, and the researcher reached a number of results, the most important of which were: - 1- The models highlighted the connotations of danger and warning, in a way that contributes to attracting attention and highlighting the dangerous effects of the philosophy of extremism and terrorism on society, (all models). After the results appeared and were discussed, the researcher reached the conclusions of the research, the most important of which are: 1- The philosophy of extremism and terrorism from the view of the graphic discourse as a negative situation is a recognition of negativity that cannot be contained, whether in terms of size or strength, and the uniqueness of such extremist acts makes them descriptible through an effective and influential graphic discourse in the recipient as a means of guidance and awareness against violence and terrorism.